113 Initial Experience With an Image-Guided Robotically Positioned Optical Platform for Aneurysm Surgery. (1st August 2016) - Kassam, Amin B.; Chakravarthi, Srikant S.; Celix, Juanita; Fukui, Melanie; Jennings, Jonathan; Walia, Sarika; Rovin, Richard A.
Abstract: INTRODUCTION: The conventional stereoscopic microscope (CS-m) made safe surgery for intracranial vascular pathology. Recently, an integrated image-guided robotic optical positioning system (ROVOT-m) has been released for clinical use. We undertook a benchside, cadaveric and clinical study to determine its applicability to aneurysm surgery. METHODS: Benchside measurements of field of view (FOV) and depth of field (DOF) were obtained for CS-m and ROVOT-m. Two cadavers were operated on to simulate aneurysm surgery using both CS-m and ROVOT-m. Clinical feasibility of ROVOT-m was demonstrated during for surgery for both ruptured and unruptured aneurysms. RESULTS: At highest magnification, ROVOT-m has a 25-mm FOV, 40% greater than that of CS-m. At the same FOV of 25 mm and working distance of 250 mm, ROVOT-m has a DOF of 14 mm, more than 3 times greater than CS-m. Cadaveric dissection confirmed that the volume of view (VOV) for the ROVOT-m was substantially larger than for the CS-m. Six aneurysms were clipped using the ROVOT-m: 4 ruptured middle cerebral artery aneurysms, 1 unruptured anterior communicating artery aneurysm, and 1 unruptured superior hypophyseal artery aneurysm. CONCLUSION: The ROVOT-m has a substantially larger VOV the volume of surgical anatomy in focus and adequately illuminated. The larger immersive volume of surgical anatomy in focus was especially valuable when temporary clipping in the cases of middle cerebral artery aneurysm as the VOV extended from proximal internal carotid artery to distal M2 branches. The use of preset positions permits multiple relevant optical trajectories to be viewed rapidly and in sequence, which is particularly beneficial for assessing clip placement. Hands-free positioning allows for uninterrupted work flow.